Spectrophotometric multicomponent analysis of a mixture of triprolidine hydrochloride and pseudoephedrine hydrochloride in pharmaceutical formulations by partial least-squares multivariate calibration - Donmez, O. Aksu; Bozdogan, A.; Kunt, G.; Div, Y. (POLSKIE TOWARZYSTWO CHEMICZNE-POLISH CHEMICAL SOCIETY, 2007)
A multivariate spectrophotometric calibration has been applied for simultaneous determination of triprolidine hydrochloride (TRP) and pseudoephedrine hydrochloride (PSE) in binary mixtures in tablets. Separation of the mixture components has been accomplished without derivatisation. For determination of the analytes, partial least-squares (PLS-2) regression analysis of spectral absorption data has been performed. Experimental calibration matrix was constructed using 9 samples, according to the full factorial design. The considered concentrations were 13, 15, 17 mu g mL(-1) for TRP, and 330, 360, 390 mu g mL(-1) for PSE. Absorbance was measured in the range 235-315 nm, each 5 nm. The results have shown that PLS-2 is a simple and accurate method for determination of TRP and PSE in pharmaceuticals.
Keywords: Triprolidine Hydrochloride; Pseudoephedrine Hydrochloride; multivariate calibrations; simultaneous determination; DEXTROMETHORPHAN; ASSAY; PARACETAMOL; REGRESSION; CAFFEINE; Chemistry